Green synthesis of zinc nanoparticles through plant extracts: establishing a novel era in cancer theranostics. (18th September 2019) - Hameed, Safia; Iqbal, Javed; Ali, Muhammad; Khalil, Ali Talha; Ahsan Abbasi, Banzeer; Numan, Muhammad; Shinwari, Zabta Khan
Abstract: Cancer represents one of the leading causes of mortalities worldwide. Recent progress in nanotechnology has opened a new avenue for research in cancer theranostics. Among the different metal oxide nanoparticles, the semiconductor zinc oxide nanoparticles have gained significant importance. Following to tremendous potential of biosynthesized metal nanoparticles as anticancer agents, there is a dire need to review the current studies available on phytogenic zinc oxide nanoparticles. We aim to bridge the knowledge vacuum and further elaborate the mechanistic as well as futuristic insights from biosynthesis to application of the phytogenic zinc oxide nanoparticles. The present manuscript is a systemic review of the research articles published in recent years by searching through different online web repositories. Furthermore, in this review, we have discussed about the recent milestones and possible hurdles for the therapies based on phytogenic zinc oxide nanoparticles.